CORRELATION OF MORBIDITY WITH SMOKING STATUS AND POSBINDU PTM TO PREPARE AGING SOCIETY HEALTH MANIFESTATION IN INDONESIA - Nastiti, Rizma Dwi; Hargono, Arief; Artanti, Kurnia Dwi; Martini, Santi; Li, Chung-Yi; Triyaniarta, Adinda Rahma (Jurnal Biometrika dan Kependudukan, 2024)
Aging increases vulnerability to diseases, necessitating comprehensive strategies promoting healthy lifestyles. Posbindu PTM (Integrated Guidance Post for NCDs) is Indonesia's community-based program which was aimed to mitigate the impact of NCDs through monitoring risk factors and empowering individuals for early intervention and lifestyle’s changes. This study examined the correlations between smoking status, and implementation of Posbindu PTM among Indonesia's elderly population with morbidity rates. Data from 34 provinces were analyzed using Spearman's correlation test (α=5%) to examine relationships between morbidity rates (dependent variable) from the 2022 Elderly Population Statistics data, smoking status (active smokers, ex-smokers, non-smokers), and the percentage of Posbindu PTM implementation (independent variables) from the data of the 2021 Indonesia Health Profile. Active smokers (p=0.007, r=0.455) and ex-smokers (p=0.003, r=0.497) showed positive correlations with morbidity, while non-smokers (p=0.002, r=-0.506) exhibited a negative correlation. Posbindu PTM implementation (66,4% average in 2021) was not significantly correlated with morbidity (p=0.367). High smoking rates among Indonesia's elderly affect morbidity levels. Posbindu PTM, as an early detection and health promotion program, has not been well-implemented nationwide. Efforts and government commitment to prioritize health promotion and prevention at the grassroots level are essential for achieving a prosperous and effective aging society.